Pengaruh limbah cair industri kerupuk kulit terhadap kualitas air Sungai Pesing, Kelurahan Segoroyoso, Bantul - Az-Zahro, Miftahul Farhana; Lukito, Herwin; Anasstasia, Titi Tiara (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
The skin crackers industry in Segoroyoso village produces liquid waste with high levels of BOD, COD, TSS, ammonia, oil and grease. There is no liquid waste processing yet. Liquid waste is dumped into the Pesing River and has the potential to cause water quality degradation. This research aims to analyze the quality of the industrial liquid waste, the river water quality status, and evaluate stream standards. The pollution index method is applied. Sampling was conducted in October 2022 through purposive sampling at the industrial outlet, river before and after the outlet, and irrigation channels. The research results that only the pH parameter meets the water quality standards in the luquid waste. River water quality shows that BOD, COD, ammonia, oil and grease at several points do not meet quality standards. The river water quality status categorized as meeting standards at point before the outlet with an IP value of 0.47 and slightly polluted at the point after the outlet and irrigation channel with IP values ​​of 4.32 and 3.49. The evaluation of stream standards reveals that COD, BOD, and ammonia do not meet river water quality standards with a value of 37.61 mg/L; 7.13 mg/L; and 0.52 mg/L.